#TITLE_ALTERNATIVE# - SHABRINA ( NIM : 10109032 ) Pembimbing : Khreshna I.A. Syuhada, M.Sc, Ph.D, AYU
Extreme value theory is a cornerstone of a method to identify extreme values and model it in a distribution. In the financial field, extreme values can occur in the decline of stock price index. Extreme values are rare but certainly have a great impact the risk of extreme losses. Efiorts to control risk is to understand and quantify the risks appropriately. Value-at-Risk (VaR) is a popular measure of risk used in financial risk management. Thus, in determining the risk of extreme value are used necessary calculations using VaR and Extreme Value Theory. Ex- treme Value Theory with Block Maxima Method identify extreme values as the maximum value of data per block period of time, thus determining the block size in this method is very important. The extreme values are modeled by a family of GEV distribution. Extreme value of the stock index's decline can be modeled with distribution Frechet. Parameter estimator of the extreme value distribution can be used in the calculation of VaR. From the calculation, the value of VaR is in uenced by the block size and the chosen level of confidence. So extreme decline in the stock index will be greater as the larger block size and confidence level.